INFLUENCER DAN PRODUK LOKAL : PERANCANGAN NARASI DAN DAMPAKNYA TERHADAP PERILAKU PEMBELIAN KONSUMEN - Edwin Perdana Wijaya; Diqbal Satyanegara; Widya Nur Bhakti Pertiwi; Dian Haerudin (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the direct influence of influencer credibility and narrative elements on the purchase decisions for local products in Indonesia, and to examine the moderating role of consumer attitude in these relationships. A quantitative approach was employed using a survey of 360 social media users in Indonesia who had purchased local products based on influencer recommendations. Data was analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that influencer credibility has a significant direct effect on purchase decisions. However, narrative elements only influence purchase decisions indirectly, fully mediated by consumer attitude. Consumer attitude itself is the strongest predictor of purchase intention and significantly moderates the relationship between influencer credibility and purchase decisions. This research provides a more nuanced model of influencer marketing effectiveness by integrating narrative transportation theory and source credibility theory within the context of local products, confirming the critical role of consumer attitude as a key mediating variable for understanding the cognitive and affective mechanisms driving consumer behavior.